Pediatric viral gastroenteritis during eight years of study. - Brandt, C D (1983)
During the period January 1974 through July 1982, fecal samples from 1,537 pediatric inpatients with gastroenteritis were tested for enteric viruses by electron microscopic and rotavirus enzyme-linked immunosorbent assay techniques. Rotaviruses were detected in 34.5% of these patients, enteric adenoviruses were detected in 4.7%, approximately 27-nm viruses were detected in 1.6%, and at least one of these agents was found in 40.1% of the study subjects. Three infections were by an apparently new agent which morphologically is a rotavirus, but which failed to react in the rotavirus enzyme-linked immunosorbent assay. During the first 8 calendar years of study, rotaviruses were detected in 39.0% of 577 patients in the even-numbered years and 30.3% of 702 patients in the odd-numbered years. Adenoviruses were found in all calendar months. Rotaviruses were found in inpatients in November through July, whereas approximately 27-nm viruses were found in October through June. The percentage of patients who had a demonstrated viral infection rose steadily from 7.4% in September to 72.0% in January and then steadily declined to 2.9% in August. Viral infection was especially common in study subjects who were 7 through 24 months of age; 61% of such children had one or more enteric viruses. Rotavirus-infected patients tended to be younger during the months of greatest rotavirus activity than at the beginning and end of the rotavirus season, presumably because of a greater exposure to virus at the height of the rotavirus outbreak.